Utopia and dystopia in Nadeem Aslam’s Maps for Lost Lovers - Mahmoud Ananzeh,; Raihanah M.M., (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article explores the themes of utopia and dystopia as depicted by Nadeem Aslam in his novel, Maps for Lost Lovers which centers on the Pakistani immigrant community in a small English town.. The town serves as a critical element, a utopia for some characters and a dystopia for others. The perception of the place depends on their adaptability or adherence to their original culture. The protagonist, Kaukab, represents the older generation, perceiving England as a Dystopia while nostalgically praising Pakistan. Despite this, her family, led by Shamas and their three children, rejects her wistful views. Instead, they view England as their utopia, embracing its freedom and distancing themselves from Pakistani traditions. Aslam's narrative underscores the idea that individuals choose their utopian or dystopian world, shaped by their traditions and minds. This article delves into the nuanced depiction of utopia and dystopia in Maps for Lost Lovers, shedding light on the complexities of cultural identity, assimilation, and the immigrant experience in the novel. While existing research focuses on the novel’s themes of migration, cultural conflict, and nostalgia, this study examines how utopia and dystopia are not just external places but deeply personal and psychological experiences